The Quantification of Tissue Sodium Concentration using 23Na-Magnetic Resonance Microscopy at 7 T: Probing the Acute Stroke Phase - WETTERLING, FRIEDRICH; FAGAN, ANDREW (My University, 2010)
Accurate identification of the potentially salvageable ischaemic penumbra is critical in identifying stroke patients who will benefit from thrombolysis and in designing future clinical trials of potential neuroprotectants. The perfusion/diffusion mismatch technique, currently used to detect penumbra is an indirect measure, lacking precision. The ability to accurately quantify TSC in vivo could allow developing of a direct bio-marker for tissue viability in stroke [1]. However, quantitative 23Na-Magnetic Resonance Microscopy (qNa-MRM) of the rat brain is challenging due to the low SNR measured in the MRM images, which results from the 23Na nucleus?s low in vivo concentration, low gyromagnetic ratio, fast transversal signal decay, and the required small voxel size (< 4 ?l).
Proceedings of 15th Scientific Meeting of International Society for Magnetic Resonance in Medicine
15th Scientific Meeting of International Society for Magnetic Resonance in Medicine
PUBLISHED
Stockholm, Sweden
Keywords: Neuroscience; MRM images; Neuroscience; Next Generation Medical Devices